PENGARUH KUALITAS BENIH JAGUNG HIBRIDA SUMO TERHADAP PENINGKATAN PENDAPATAN PETANI JAGUNG (STUDI PADA MASYARAKAT MUSLIM DI KECAMATAN AWANGPONE) - Bettare, Nurlinda; Abdibuhasyim, Muhammad (Institut Agama Islam Negeri (IAIN) Bone, 2023)
Corn farming is growing rapidly and getting various responses from farmers. This commodity needs to be accelerated in its development to meet the ever-increasing demand. In this case the researcher intends to examine the effect of the quality of the sumo hybrid corn seeds on increasing the income of corn farmers in Awangpone District. The approach in this study used a quantitative approach with the type of field research by observing or observing first then giving a questionnaire in the form of questions to 50 samples according to the data needed then the results of the research data were analyzed and described to see further about the influence of the quality of the sumo hybrid corn seeds to increase the income of corn farmers. The results of the study showed that there was a significant and positive effect of the quality of hybrid sumo corn seeds on increasing the income of corn farmers in Awangpone District. By having a good level of understanding about the quality of hybrid sumo corn seeds, farmers will be able to increase their income. Be able to distinguish the quality of the seeds that will be used. The quality of the sumo hybrid corn seeds affects the income of corn farmers and will increase the welfare of farmers in Awangpone District by 68% and the remaining 32% is influenced by other variables outside the research model.Keywords: quality of sumo hybrid corn seeds, income, Muslim farmersAbstrakUsaha tani jagung berkembang pesat dan mendapat beragam respon dari petani. Komoditas ini perlu di pacu perkembangannya untuk memenuhi kebutuhan yang terus meningkat. Dalam hal ini peneliti bermaksud untuk meneliti mengenai pengaruh kualitas benih jagung hibrida sumo terhadap peningkatan pendapatan petani jagung di Kecamatan Awangpone. Pendekatan pada penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian lapangan dengan cara observasi atau pengamatan terlebih dahulu kemudian memberikan angket berupa pertanyaan kepada 50 sampel yang sesuai dengan data yang dibutuhkan kemudian hasil data penelitian dianalisis dan dideskripsikan untuk melihat lebih jauh mengenai pengaruh kualitas benih jagung hibrida sumo terhadap peningkatan pendapatan petani jagung. Adapun hasil penelitian menunjukkan Terdapat pengaruh kualitas benih jagung hibrida sumo yang signifikan dan positif terhadap peningkatan pendapatan petani jagung di Kecamatan Awangpone. Dengan memiliki tingkat pemahaman mengenai kualitas benih jagung hibrida sumo yang baik, para petani akan mampu meningkatkan pendapatannya. Mampu membedakan kualitas benih yang akan di gunakan. Kualitas benih jagung hibrida sumo mempengaruhi pendapatan petani jagung dan akan meninsgkatkan kesejahtraan petani di Kecamatan Awangpone sebesar 68% dan sisanya 32% dipengaruhi oleh variabel lain di luar model penelitian.